"Where Am I": Characterization of Ultra-Wide Band Real Time Location System in Line of Sight - Mahasan Mat Ali; Syamimi Shamsuddin; Mohd Nazrin Muhammad; Sayed Kushairi Sayed Nordin; Shariman Abdullah (Engineering Science Letter, 2025)
Absolute position measurement is a necessity in an Autonomous Indoor Mobile Robot (AiMR) built as to compensate the systematic and non-systematic errors caused by the odometry. This paper is set out to characterize the range bias of DecaWave Trek 1000 in Line of Sight (LOS). DecaWave Trek 1000 is a commercially available Real Time Location System (RTLS) based on Ultra-Wide Band (UWB) technology. The main advantage of using such a system is it provide quick solution with best-in-class accuracy of up to +10 cm. The system also compliant with IEEE802.15.4-2011 standards and implemented based on CMOS technology. To validate its performance, four distinct environment scenarios were selected based on their spatial occupancies to represent both favourable and non-favourable operating conditions. A total of 120,000 positioning data were measured and recorded throughout this study. Firstly, the collected data were compared to the ground truth and subjected to statistical analysis to determine whether environment factors significantly influenced ranging errors. Then the range error the results confirm that while the system performs within its specified accuracy under favourable conditions, the non-favourable condition on the other hand shows a drop of 20% in ranging accuracy. Throughout this extensive characterization, a systematic error model and noise estimation were formulated, providing a critical foundation for integrating UWB RTLS measurements into advanced probabilistic localization framework. Looking forward, the developed characterization function, offers strong potential for fusion with filtering algorithm such as Bayesian filters to enhance indoor navigation reliability for an AiMR application.